The factors that influence the company to switch public accounting firm - Riswandhita, Yanuar; Sugeng (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2022)
The relationship between a company and a public accounting firm will experience various twists and turns that determine whether the engagement relationship between a company and a public accounting firm can continue or not. The company's decision to terminate the engagement and change the accounting firm can also occur voluntarily due to the KAP's reputation, audit opinion, company size and company's financial condition. The purpose of this study is to analyze the factors that influence companies to switch public accounting firms to manufacturing companies in the consumer goods sector listed on the Indonesian stock exchange in 2017-2019. The research technique used in this research is the associative method with the research approach used is a quantitative approach. The population in this study were all manufacturing companies listed on the Indonesia Stock Exchange from 2017 to 2019. The research sample was taken by purposive sampling so that a sample of 24 companies was obtained with period 3 obtained 72 data. The analysis technique used in this study was regression. multiple linear. After testing, it was found that the variable of the company's financial condition had an effect on the company moving to a public accounting firm, while the other variables had no effect.